1972
DOI: 10.1042/cs0420685
|View full text |Cite
|
Sign up to set email alerts
|

Renin and Control of Arterial Blood Pressure during Terminal Renal Failure Treated by Haemodialysis and by Transplantation

Abstract: 1. Plasma renin concentrations were determined in 1068 samples obtained in 113 patients in the end stage of chronic renal failure treated by repeated haemodialyses or by renal transplantation. 2. Patients with malignant nephroangiosclerosis have a very high concentration of plasma renin; this differentiates them from other disease groups, where renin concentration is sometimes normal and sometimes elevated; there is no significant difference between the glomerulonephritis and pyelonephritis grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
1
2

Year Published

1973
1973
1980
1980

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 1 publication
0
11
1
2
Order By: Relevance
“…Whereas Wilkinson et al [45] found a close correlation of blood pressure and renin in their pa tients, this could not be demonstrated by others [39,44]. Furthermore, we did not find a significant inverse relation of PRA to fluid spaces [11,44] or plasma sodium [39].…”
Section: Hypertension In Renal Failurecontrasting
confidence: 99%
See 2 more Smart Citations
“…Whereas Wilkinson et al [45] found a close correlation of blood pressure and renin in their pa tients, this could not be demonstrated by others [39,44]. Furthermore, we did not find a significant inverse relation of PRA to fluid spaces [11,44] or plasma sodium [39].…”
Section: Hypertension In Renal Failurecontrasting
confidence: 99%
“…Whereas Wilkinson et al [45] found a close correlation of blood pressure and renin in their pa tients, this could not be demonstrated by others [39,44]. Furthermore, we did not find a significant inverse relation of PRA to fluid spaces [11,44] or plasma sodium [39]. Thus, alternative mechanisms of blood pressure regulation in patients on maintenance dialysis have to be considered: (I) autonomic vascular factors [16]; (2) dysfunction of baroceptors [22,30]; (3) disturbance of the hypotensive prostaglandin-kinin system [19], and (4) disturbance of the sympathetic system [3,22].…”
Section: Hypertension In Renal Failurementioning
confidence: 56%
See 1 more Smart Citation
“…In 21 patients the increase in PRA after dialysis, correlated negatively with the change in systolic blood pressure [9], In 16 patients the change in PRA due to dialysis was nega tively correlated with the variation in body weight [3]. In 21 patients dialysis resulted in a mean increase in PRA by a factor of 1.4 [8].…”
Section: Discussionmentioning
confidence: 95%
“…Most of the reported studies dealt with long-term blood pressure regulation and as sessed the influence of chronic hemodialysis on blood pressure, plasma renin activity (PRA) and body fluid compartments, but contain only scattered information regarding the influence of acute volume changes [2][3][4]6,8,9,11], In the present study, the effects of one dialysis session and of subsequent loading by 1.5-2 liters saline on body fluid compartments. PRA and blood pressure were studied in patients, attending a chronic hemodialysis program.…”
Section: Introductionmentioning
confidence: 99%